Samsarah in Insurance Marketing: A Case Study of Family Takaful Insurance - Adrian, Adrian; Asmuni, Asmuni; Muhammad, Hasman; Andriani, Novi; Nurhayati, Umi (Research Horizon, 2023)
This study aims to delve deeper into the subject of samsarah in insurance marketing, with a specific focus on family takaful insurance companies. The research methodology involves conducting a literature review by collecting relevant materials and examining all sources pertaining to the laws of family takaful insurance. Subsequently, the collected data will be carefully analyzed to distinguish between information considered accurate and inaccurate. The findings of this study indicate that the system employed in family takaful is genuinely based on cooperation (tabarru). Family takaful insurance applies a risk-sharing principle that is materialized through the collection of tabarru funds, fostering solidarity, mutual protection, and strong bonds among participants. The role of a family takaful insurance agent extends beyond merely selling takaful products. They provide valuable assistance by sharing information with insurance participants. This may include organizing workshops that highlight the advantages and benefits of family takaful insurance. These workshops serve to enhance participants' understanding and confidence in the knowledge conveyed by sharia-compliant insurance agents, thereby increasing awareness of the significance of the benefits associated with family takaful insurance.